Policy Challenges in the Gulf Cooperation Council Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
The Gulf Cooperation Council (GCC) countries face important policy challenges and opportunities. This paper covers the economic developments and policies since 1980; the impact of the GCC's external environment; the medium-term economic prospects; the broad outlines of a common adjustment and reform strategy, and the implications of adjustment in the GCC countries on the rest of the Middle East and North Africa region.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet